Effects of buckwheat and millet flour addition on the antioxidant potential of wheat flour and rheological properties of the dough - Rakin Marica B.; Zarić Danica B.; Krunić Tanja Ž.; Bulatović Maja Lj. (Hemijska Industrija, 2025)
In this work, the antioxidant properties of three types of flour (wheat, buckwheat and millet flour) and rheological properties of three types of dough were investigated: wheat flour dough, dough obtained from a mixture of 50 wt.% wheat flour and 50 wt.% buckwheat flour and dough obtained from a mixture of 50 wt.% wheat flour and 50 wt.% millet flour. Polyphenol content and antioxidant tests have shown that buckwheat flour is superior to wheat and millet flour. The antioxidant activity expressed by the 2,2-diphenyl-1-picrylhydrazyl radical scavenging activity did not correlate with the content of polyphenols, which is a consequence of the presence of tannins and phytic acid in millet flour. Determination of rheological properties was performed by a universal dough characterizer. The substitution of wheat flour with buckwheat and millet flour leads to a weakening of the protein structure. Furthermore, the addition of buckwheat or millet flour reduces the rate of gelatinization and viscosity and has a positive effect on the reduction of retrogradation. The combination of these two types of flour with wheat flour can reduce the aging of bakery products.